EFL COLLEGE STUDENTS’ UNDERSTANDING AND USE OF NOUNS, VERBS, AND ADJECTIVES: EXAMINING WORD CLASS AWARENESS IN WRITING - Silmawati Silmawati; Puan Tursina (Journal Informatic, Education and Management (JIEM), 2026)
This study examines EFL college students’ understanding and use of nouns, verbs, and adjectives in writing, with a focus on word class awareness. A mixed-methods design was employed involving 63 second-semester students from STKIP Muhammadiyah Aceh Barat Daya. Data were collected through a 15-item grammar test, a writing task (sentence construction and paragraph writing), and open-ended awareness questions. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results showed that students demonstrated a high level of understanding of nouns, verbs, and adjectives, with correct responses ranging from 82.8% to 100%. Noun and verb items showed slightly higher accuracy, while adjective-related items were relatively more challenging. In the writing task, most students were able to apply word class knowledge effectively in sentence and paragraph writing, although one student showed low performance. The awareness data indicated that all students understood the differences among word classes; however, adjectives were perceived as the most difficult category due to confusion with adverbs, adjective order, and limited vocabulary. Overall, the findings suggest that although students possess strong grammatical knowledge, adjective usage remains the most challenging area in both understanding and application. This highlights the need for integrating explicit grammar instruction with contextual writing practice.